Dynamic Chiral Metasurfaces for Broadband Phase‐Gradient Holographic Displays (Advanced Optical Materials 5/2023). Issue 5 (3rd March 2023) - Naeem, Taimoor; Kim, Joohoon; Khaliq, Hafiz Saad; Seong, Junhwa; Chani, Muhammad Tariq Saeed; Tauqeer, Tauseef; Mehmood, Muhammad Qasim; Massoud, Yehia; Rho, Junsuk
Abstract : Dynamic next‐generation holography based on photonic integrated circuits (PICs) technology has significant potential in medical science, virtual reality, intelligent data security, and encryption, etc. The work presented by Yehia Massoud, Junsuk Rho, Muhammad Qasim Mehmood, and co‐workers in article number 2202278 features a chiral metasurface integrated with a liquid crystal cell that provides dynamic phase‐gradient holographic displays at broadband visible wavelengths. The designed metasurface is controlled by an externally applied voltage to reproduce spin‐dependent switching holographic information.